2000
DOI: 10.1111/j.1365-313x.2000.00895.x
|View full text |Cite
|
Sign up to set email alerts
|

A member of a novel Arabidopsis thaliana gene family of candidate Mg2+ ion transporters complements a yeast mitochondrial group II intron‐splicing mutant

Abstract: Summary Autocatalytic activity of some group II introns has been demonstrated in vitro, but helper functions such as the yeast MRS2 protein are essential for splicing in vivo. In our search for such helper factors in plants, we pursued the cloning of two Arabidopsis thaliana homologues, atmrs2‐1 and atmrs2‐2. Atmrs2‐1, but not atmrs2‐2, complements the yeast deletion mutant of mrs2, and this is congruent with the prediction of two adjacent transmembrane stretches in AtMRS2‐1 and yeast MRS2 but not in AtMRS2‐2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 35 publications
(54 reference statements)
0
50
0
Order By: Relevance
“…In higher plants, CorA-like Mg 2+ transporter family (At-MGT) has been identified from Arabidopsis thaliana and consists of at least 10 members. Two of the family members, AtMGT1 and AtMGT10, were experimentally confirmed to function as high-affinity Mg 2+ transporters [12,13]. AtMGT5 was identified to function as a dual-functional Mg 2+ -transporter mediating both influx and efflux [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In higher plants, CorA-like Mg 2+ transporter family (At-MGT) has been identified from Arabidopsis thaliana and consists of at least 10 members. Two of the family members, AtMGT1 and AtMGT10, were experimentally confirmed to function as high-affinity Mg 2+ transporters [12,13]. AtMGT5 was identified to function as a dual-functional Mg 2+ -transporter mediating both influx and efflux [22].…”
Section: Discussionmentioning
confidence: 99%
“…The At-MGT1 was localized in plant plasma membrane [12] and AtMGT10 (also known as AtMRS2-11) was localized in plant chloroplast envelope membrane system [21], implicating its role in Mg 2+ uptake and translocation into chloroplasts. A third member, AtMGT2 (also known as At-MRS2-1), complements the yeast deletion mutant mrs2 and restores the intramitochondrial Mg 2+ concentration to nearly wild-type level [13]. Very recently, Li et al [22] identified the fourth member AtMGT5, functioning as a dual-functional Mg 2+ -transporter that mediates uptake or efflux in a concentration-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher plant transporters of the CorA/MRS2 family were first identified in 2000, when Schock et al [6] reported a gene family of ten members in Arabidopsis thaliana, named AtMRS2-1 to AtMRS2-10. These authors also demonstrated that AtMRS2-1 functionally complements Mrs2-deficient yeast restoring intramitochondrial Mg 2+ concentration to the wild-type level.…”
mentioning
confidence: 99%